Hipertiroid dalam Kehamilan - Suparman, Erna (e-CliniC, 2021)
Abstract: Hyperthyroidism in pregnancy could be a hyperthyroid condition that occurred before the pregnancy or acquired during the pregnancy. Hyperthyroidism in pregnancy is associated with adverse conditions for the fetus, mother, and also products of conception. The incidence for hyperthyroidism in pregnancy varies, ranging from 2-17 in 1000 births and accounts for 1-3% for all hyperthyroid cases. Clinical symptoms of hyperthyroidism in pregnancy also varies. Hyperthyroidism in pregnancy sometimes is hard to diagnose because it overlaps with normal pregnancy signs and symptoms. Clinical symptoms that might be found are tachycardia, thyromegaly, exophthalmos, and difficulty to gain weight with adequate food intake. Untreated hyperthyroidism could lead to preeclampsia and congestive heart failure for the mother, and miscarriage, placental abruption, and preterm birth. Therefore, maintaining euthyroidism on a patient is very important. Proper management of hyperthyroidism in pregnancy is very important for both mother and the fetus. Untreated hyperthyroidism could lead to pregnancy-related complications, such as premature birth, growth restriction, and even fetal death.Keywords: hyperthyroidism; pregnancyÂ Â Abstrak: Hipertiroid dalam kehamilan dapat merupakan kondisi hipertiroid yang telah ada sebelum terjadi kehamilan, atau kondisi yang didapatkan selama masa kehamilan.Hipertiroid dalam kehamilan dikaitkan dengan kondisi yang merugikan janin, ibu, dan hasil kandungan. Insidensi hipertiroid dalam kehamilan bervariasi, yaitu sekitar 2-17 dalam 1000 kelahiran serta merupakan 1%-3% dari jumlah kasus hipertiroid.Gejala klinis hipertiroid dalam kehamilan bervariasi. Pada kondisi hipertiroid dalam kehamilan, mungkin akan terdapat kesulitan dalam diagnosis, mengingat gejala-gejala dan tanda-tanda yang muncul saat terjadi kehamilan normal.2 Gejala klinis yang mungkin ditemukan ialah takikardia, tiromegali, eksoftalmos, dan tidak bertambahnya berat badan dengan asupan makanan yang memadai. Hipertiroid dalam kehamilan yang tidak ditangani dapat memicu preeklampsia dan gagal jantung kongestif pada ibu, serta meningkatkan risiko keguguran, solusio plasenta dan kelahiran prematur. Oleh karena itu mempertahankan eutiroidisme pada pasien sangatlah penting. Penatalaksanaan hipertiroid yang tepat selama kehamilan sangat penting bagi ibu dan janinnya. Hipertiroid yang tidak diobati dapat menyebabkan komplikasi terkait kehamilan seperti kelahiran prematur, hambatan pertumbuhan, dan bahkan kematian janin.Kata kunci: hipertiroid; kehamilan